2018
DOI: 10.4066/biomedicalresearch.29-16-2064
|View full text |Cite
|
Sign up to set email alerts
|

Application of holistic nursing in care for cranial neurointervention

Abstract: Objective: To explore the application and clinical value of holistic nursing in care for cranial neurointervention. Methods: A total of 138 patients needed the treatment of cranial neurointervention, who were admitted in dept. of neurosurgery in our hospital from August 2015 to January 2016, were divided into routine nursing group (control group) and holistic nursing group (observation group), 69 patients a group. After treatment and nursing, the improvement of life quality, occurrence of complications, averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Another study conducted by McEvoy & Duffy () determined that a holistic approach enables the adaptation of patients and their families to the disease, increases the quality of life of the patients and ensures patients’ well‐being, growth and empowerment. Lu () reported that holistic nursing practices improve the quality of care and satisfaction in patients and staff equally. Another study identified that the holistic approach can contribute to the development of an organizational culture (Bonczek et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted by McEvoy & Duffy () determined that a holistic approach enables the adaptation of patients and their families to the disease, increases the quality of life of the patients and ensures patients’ well‐being, growth and empowerment. Lu () reported that holistic nursing practices improve the quality of care and satisfaction in patients and staff equally. Another study identified that the holistic approach can contribute to the development of an organizational culture (Bonczek et al.…”
Section: Introductionmentioning
confidence: 99%
“…In literature stated that nurses' patient-centered care competence and holistic nursing competence levels were high [16][17][18]. Lu (2018) reported that holistic nursing practices improve the quality of care and satisfaction in patients [19]. Additionally, Aydın and Hicdurmaz (2019) stated that holistic nursing is an essential element of nursing care, as it enhances the quality of nursing care [20].…”
Section: Introductionmentioning
confidence: 99%